Work-Life Balance, Workload, and Turnover Intention: An Empirical Study on a Local State-Owned Enterprise in Indonesia - Zaid Ilfan; Fetty Poerwita Sary (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Employee turnover rates at Perumda Dharma Jaya have risen sharply over the past five years, alongside indications of excessive workloads reflected in overtime hours that far exceed labor regulations. This study analyzes the effects of work-life balance and workload on employees’ turnover intentions at Perumda Dharma Jaya, both partially and simultaneously. The study uses a quantitative, explanatory research methodology, involving 100 respondents selected via purposive sampling from a population of 500 active employees. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that work-life balance has a significant negative effect on turnover intention, whereas workload has a significant positive effect. Simultaneously, both variables were found to have a significant effect on turnover intention, accounting for 88.1 percent of the variance. These findings confirm that appropriately managing workloads and supporting employees’ work-life balance are key determinants that Perumda Dharma Jaya’s management must prioritize to reduce future employee turnover.